Peranan Filsafat dalam Penginjilan - Paulus Eppang (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The main focus of this research is to explain the role of philosophy in evangelism. This is done, there are findings of problems that view philosophy with suspicion and are advised to avoid it, besides that philosophy is considered as the work of the devil that can distort one's faith in Christ. To examine this, here uses an analytical method on the history of Christian philosophy with a qualitative method approach. The purpose of this research is to prove that philosophy does not deviate Christians from their faith, philosophy is also not the work of the devil and does not need to be viewed negatively or avoided, but philosophy can actually be used and plays a role in preaching the gospel of Jesus Christ to people who find it difficult to believe and demand there is scientific evidence against his mind regarding the gospel of Jesus Christ. The conclusion of this research is that philosophy can play a role in bridging difficulties in preaching the gospel, philosophy can be used to play a role in expanding the preaching of the gospel and philosophy can also help in giving accountability for the gospel message that is conveyed.